2012
DOI: 10.1063/1.3676042
|View full text |Cite
|
Sign up to set email alerts
|

Graphene covered SiC powder as advanced photocatalytic material

Abstract: Graphene covered SiC powder (GCSP) has been fabricated by well established method of high temperature thermal decomposition of SiC. The structural and photocatalystic characteristics of the prepared GCSP were investigated and compared with that of the pristine SiC powder. Under UV illumination, more than 100% enhancement in photocatalystic activity is achieved in degradation of Rhodamine B (Rh B) by GCSP catalyst than by pristine SiC powder. The possible mechanisms underlining the observed results are discusse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
54
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(57 citation statements)
references
References 30 publications
3
54
0
Order By: Relevance
“…They usually start at the edges of large defects. These features are consistent with the ridges and wrinkles reported in earlier studies [19], which are usually observed on graphene grown on SiC surface [16] due to the large difference in thermal expansion coefficient between epitaxial graphene layers and SiC. Fig.…”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…They usually start at the edges of large defects. These features are consistent with the ridges and wrinkles reported in earlier studies [19], which are usually observed on graphene grown on SiC surface [16] due to the large difference in thermal expansion coefficient between epitaxial graphene layers and SiC. Fig.…”
Section: Resultssupporting
confidence: 81%
“…Оf course, expensive singlecrystal SiC substrates of large diameter are required to obtain graphene of good quality. However, an approach that uses polycrystalline or amorphous SiC for synthesis of graphene micro-and nanocomposites could be used as an alternative technique [16,17] .The advantage of this approach is the large-scale production of graphene at low cost.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the energy band structure of 3C-SiC satisfies the prerequisites of water splitting reaction very well [20][21][22]. Most importantly, 3C-SiC is remarkable for its good stability, low-cost and it can be easily fabricated [23][24][25][26][27]. Therefore, it does not come as a surprise that many theoretical and experimental studies have explored the catalytic water splitting performance of silicon carbide.…”
Section: Introductionmentioning
confidence: 99%
“…Zhiyu Gong, 1 Shuo Chang, 1 Fei Ye, 1 Tianxing Wang, 1 Wangsheng Chu, 1 Chongwen Zou, 1 In the past years, tremendous attention has been paid to resolving the increasingly serious energy and environment problems by exploring various solar-driven photocatalysts. 1,2 Among various candidates, transition metal dichalcogenide (TMC) is one of ideal catalysts because of its excellent absorption on visible-light region and extensive source.…”
mentioning
confidence: 99%
“…1,2 Among various candidates, transition metal dichalcogenide (TMC) is one of ideal catalysts because of its excellent absorption on visible-light region and extensive source. 3,4 Many efforts have been put into exploring different approaches to prepare TMC nanocrystals with various structures.…”
mentioning
confidence: 99%